The academic profession as an object of study in Mexican teacher training schools - Del Cid García, Carlos Javier (IE Revista de Investigación Educativa de la REDIECH, 2025)
The aim of this paper is to describe some central elements for the construction of the academic profession in teacher training schools as an object of study. The formulation of this work arises from the need to identify the processes of reconfiguration of the academic and professional profile of teacher educators, as well as the characteristics of academic work in teacher training institutions. The proposal is structured in three sections: the first one seeks to problematize the changes in the academic profession and activities in teacher training schools. The second section exposes the knowledge gap left by national studies on the academic profession in Mexico. The third section develops the argumentation on the perspective of analysis of the academic profession in teacher training schools. The need to understand the professional status of the trainer of trainers from the theoretical perspective of the academic profession is raised. Finally, we conclude that it is crucial to generate theoretical and methodological perspectives that allow us to understand the specific characteristics of the academic profession in this institutions and that these can serve as input for the design and implementation of policies that maintain relevance and effectiveness in these institutional contexts.